2022
DOI: 10.1177/17562848221127474
|View full text |Cite
|
Sign up to set email alerts
|

Associations between inflammatory bowel disease, social isolation, and mortality: evidence from a longitudinal cohort study

Abstract: Background: Social well-being of patients with inflammatory bowel disease (IBD) is garnering increased attention; however, the impact of social isolation remained poorly understood. Objectives: We investigated the joint association of social isolation and IBD with premature deaths to articulate the profound impact of social isolation in IBD prognosis. Design: Longitudinal cohort study. Methods: We leveraged data of 486,014 participants from UK Biobank (including 5791 with IBD), the mean follow-up was 11.84 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Another important phenomenon in the incidence of IBD is its genetic tendency; it is not only a polygenic disease but also a genetically heterogeneous disease (caused by different genes in different people). 18 Therefore, patients with IBD often feel sorry for themselves and lack confidence. The results of this study showed that, in the control group, the face, avoidance and yield scores were 19.10 ± 3.16, 16.69 ± 2.03 and 9.83 ± 3.04, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another important phenomenon in the incidence of IBD is its genetic tendency; it is not only a polygenic disease but also a genetically heterogeneous disease (caused by different genes in different people). 18 Therefore, patients with IBD often feel sorry for themselves and lack confidence. The results of this study showed that, in the control group, the face, avoidance and yield scores were 19.10 ± 3.16, 16.69 ± 2.03 and 9.83 ± 3.04, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with IBD have been reported to be at high risk for social isolation due to the stress associated with the disease, negative patient perception of social support systems and social stigma resulting from lack of public awareness. In one study with a mean follow-up period of 11.84 years, Cox proportional risk assessment showed that IBD patients who were socially isolated had a 69% increased risk of premature death compared with IBD/CD/ulcerative colitis (UC) patients who were not socially isolated, and this risk was more strongly associated with the CD subtype [ 47 ]. In the meta-IVW analysis, gene-predicted IBD was associated with depression [ 48 ].…”
Section: Promotes the Development Of Breast Cancer Through The Brain–...mentioning
confidence: 99%